Illegal Sand and Stone Mining in Rejosari, Gunung Kidul: The Erosion of Community Cohesion and Cultural Values Amid Livelihood Shifts - Novitri, Chery Maria; Riana, Ana (Sahabat Akademia Group, 2025)
This study aims to address a gap in literature by providing an in-depth analysis of the social and cultural dynamics of communities affected by illegal sand and stone mining in Gunung Kidul Regency. It focuses on shifts in livelihood patterns, cultural values, and adaptive mechanisms that emerge amid illegal mining activities. The central argument is that such practices foster social polarization, fragile economic dependence, and the erosion of community cohesion. Employing a qualitative ethnographic approach, the research explores the everyday lives of affected residents. Data were gathered through participant observation and in-depth interviews with key informants, including community leaders, village heads, and residents either involved in or impacted by mining. Additional supporting data were obtained from document studies. The data analysis followed an interactive process consisting of data reduction, display, and conclusion drawing. The study reveals that illegal mining has transformed the community’s economic structure from traditional agriculture to mining dependency, generating quick but unstable income. This shift has triggered social conflicts and polarization between pro- and anti-mining groups; undermining long-standing social cohesion rooted in cooperation. Furthermore, cultural values that emphasize respect for nature are increasingly eroded. Practically, the findings highlight that law enforcement alone is insufficient to address the issue. A comprehensive response should integrate local economic diversification, community empowerment, and the restoration of social cohesion.